Anaplasma phagocytophilum Induces TLR- and MyD88-Dependent Signaling in In Vitro Generated Murine Neutrophils - Müller, Beate J.; Westheider, Arne; Birkner, Katharina; Seelig, Birte; Kirschnek, Susanne; Bogdan, Christian; von Loewenich, Friederike D. (Frontiers in Cellular and Infection Microbiology, 2021)
Anaplasma phagocytophilum is a tick-transmitted obligate intracellular Gram-negative bacterium that replicates in neutrophils. It elicits febrile disease in humans and in animals. In a mouse model, elimination of A. phagocytophilum required CD4+ T cells, but was independent of IFN-γ and other classical antibacterial effector mechanisms. Further, mice deficient for immune recognition and signaling via Toll-like receptor (TLR) 2, TLR4 or MyD88 were unimpaired in pathogen control. In contrast, animals lacking adaptor molecules of Nod-like receptors (NLR) such as RIP2 or ASC showed delayed clearance of A. phagocytophilum. In the present study, we investigated the contribution of further PRR pathways to the control of A. phagocytophilum in vivo. Mice deficient for the NLR NOD2 had elevated bacterial loads in the early phase of infection, but were unimpaired in pathogen elimination. In contrast, animals lacking adaptor proteins of different C-type lectin receptors (CLR) such as DAP12, Fc-receptor γ-chain (FcRγ) and SYK controlled A. phagocytophilum as efficiently as wild-type mice. Further, we investigated which PRR pathways are involved in the sensing of A. phagocytophilum by in vitro generated Hoxb8 murine neutrophils. In vitro, recognition of A. phagocytophilum by murine neutrophils was dependent on TLR- and MyD88 signaling. However, it remained intact in the absence of the NLR NOD1, NOD2 and NALP3 and of the CLR adaptor molecules DAP12 and FcRγ. From these results, we conclude that TLR rather than NLR or CLR are critical for the detection of A. phagocytophilum by neutrophils although in vivo defective TLR-signaling is compensated probably because of the redundancy of the immune system.